2018
DOI: 10.1002/ijc.31352
|View full text |Cite
|
Sign up to set email alerts
|

Etiology of hormone receptor positive breast cancer differs by levels of histologic grade and proliferation

Abstract: Limited epidemiological evidence suggests that the etiology of hormone receptor positive (HR+) breast cancer may differ by levels of histologic grade and proliferation. We pooled risk factor and pathology data on 5,905 HR+ breast cancer cases and 26,281 controls from 11 epidemiological studies. Proliferation was determined by centralized automated measures of KI67 in tissue microarrays. Odds ratios (OR), 95% confidence intervals (CI) and p‐values for case–case and case–control comparisons for risk factors in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…We categorized risk factors based on what is the convention for each variable and in accordance with what has been published in large-scale studies of breast cancer [ 18 , 26 ]. We categorized age at menarche [≤12 years (early menarche), 13, 14 and ≥ 15 years (late menarche)]; family history of breast cancer in a first-degree relative [yes and no]; age at FFP [< 21, 21–24.9, 25–30, > 30 years] and age at menopause [≤ 50 and > 50 years] similarly as in previously published articles [ 18 , 26 ]. For BMI, we adopted the World Health Organization classification [< 18.5 kg/m 2 (underweight); 18.5–24.9 kg/m 2 (normal weight); 25–29.9 kg/m 2 (overweight) and ≥ 30 kg/m 2 (obese)].…”
Section: Methodsmentioning
confidence: 99%
“…We categorized risk factors based on what is the convention for each variable and in accordance with what has been published in large-scale studies of breast cancer [ 18 , 26 ]. We categorized age at menarche [≤12 years (early menarche), 13, 14 and ≥ 15 years (late menarche)]; family history of breast cancer in a first-degree relative [yes and no]; age at FFP [< 21, 21–24.9, 25–30, > 30 years] and age at menopause [≤ 50 and > 50 years] similarly as in previously published articles [ 18 , 26 ]. For BMI, we adopted the World Health Organization classification [< 18.5 kg/m 2 (underweight); 18.5–24.9 kg/m 2 (normal weight); 25–29.9 kg/m 2 (overweight) and ≥ 30 kg/m 2 (obese)].…”
Section: Methodsmentioning
confidence: 99%
“…In general, younger women were more likely to have higher-stage and higher-grade disease [12]. The previous studies have found associations between high BMI and high histologic grade levels [13,14]. The previous study implies that excess body weight contributes to higher tumor stage and grade, including a greater incidence of metastases, specifically in the 80% of breast tumors considered luminal [15].…”
Section: Research Articlementioning
confidence: 90%
“…In most studies, risk estimates for the relationship between body mass index (BMI) and breast cancer have been adjusted for tumor characteristics (stage at diagnosis and/or tumor size, grade, and nodal status) [15]. Also, obesity is associated with greater size, stage, and grade [13,16]. Numerous studies have documented that young women were more likely to develop more aggressive breast cancer subtypes with unfavorable prognostic features and present with more advanced disease stages [12].…”
Section: Research Articlementioning
confidence: 99%
“…In general, most previous studies examining the relationships between breast cancer risk factors and tumor behavior have focused on the individual tumor characteristics, and not their constellation. Higher BMI, for instance, is reportedly associated with higher grade or larger size tumors; nulliparity and menopausal hormone therapy use (MHT) with highly proliferating and lobular carcinomas, respectively; and higher parity with P53 expressing tumors [ 9 12 ]. The impact of these factors on prognostic biomarkers that combine several tumor characteristics to infer tumor aggressiveness and aid treatment recommendation is, however, less well-studied.…”
Section: Introductionmentioning
confidence: 99%